2017
DOI: 10.1108/jd-02-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Music questions in social Q&A: an analysis of Yahoo! Answers

Abstract: Purpose -Social question and answer (social Q&A) sites have become a popular tool for obtaining music information. This paper investigates what users ask about, what experience the questions convey, and how users specify their questions.Design/methodology/approach -A total of 3897 music questions from the social Q&A site Yahoo! Answers were categorized according to their question type, user experience, and question specification.Findings -The music questions were diverse with (dis)approval (42%), factual (21%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 38 publications
(78 reference statements)
1
23
0
Order By: Relevance
“…The accuracy of the answers given on Yahoo Answers has been assessed for medical topics (Ohigashi et al, 2017), as discussed above for YouTube and Wikipedia. In contrast, music-related answers have been investigated from an information behaviour perspective, focusing on the types of questions asked and the types of answers given (Hertzum;Borlund, 2017). Also in contrast, the knowledge present in Yahoo Answers has been analysed from a Wikipedia-like perspective (Shen; Li; Liu; Grant, 2015).…”
Section: Yahoomentioning
confidence: 99%
“…The accuracy of the answers given on Yahoo Answers has been assessed for medical topics (Ohigashi et al, 2017), as discussed above for YouTube and Wikipedia. In contrast, music-related answers have been investigated from an information behaviour perspective, focusing on the types of questions asked and the types of answers given (Hertzum;Borlund, 2017). Also in contrast, the knowledge present in Yahoo Answers has been analysed from a Wikipedia-like perspective (Shen; Li; Liu; Grant, 2015).…”
Section: Yahoomentioning
confidence: 99%
“…In the studies on information content, scholars often investigated question types and answer features. In line with the study of Harper et al (2010), Hertzum et al (2017) categorized music-related questions on Yahoo answers into six types, including advice, identification, (dis)approval, quality, prescriptive, and factual. Bae et al (2017) investigated the features of the answers that questioners want on social Q&A.…”
Section: Information Behaviour On Social Qanda Sitesmentioning
confidence: 99%
“…Stieglitz et al (2013) pointed out that the positive or negative sentiment in political Twitter messages are significantly related to retweet behaviour not only the quantity but also the speed. Hertzum et al (2017) examined senso-emotional experience user experience conveyed in the questions on social Q&A sites. They found that 12% of the 3897 music questions on Yahoo Answers embodied the questioner's personal emotion, albeit unrelated to gender differences.…”
Section: Emotional Expressionmentioning
confidence: 99%
See 2 more Smart Citations